2010
DOI: 10.3109/02841861003610192
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of a short stay admission programme for breast cancer surgery

Abstract: A short stay programme as implemented is cost-effective compared with care as usual. In achieving good and more efficient quality of care, larger scale implementation is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…Overrunning theatre lists as a cause of overnight admission have been reported also by others (17). Nevertheless, our finding is in line with other studies on DS management of breast cancer which reported same-day discharge rates ranging from 86% to 100% (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). However, there is one small randomized study reporting lower rate of discharge on the same day of surgery (47%) mainly due to axillary clearance following frozen section evaluation of the sentinel nodes (27).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Overrunning theatre lists as a cause of overnight admission have been reported also by others (17). Nevertheless, our finding is in line with other studies on DS management of breast cancer which reported same-day discharge rates ranging from 86% to 100% (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). However, there is one small randomized study reporting lower rate of discharge on the same day of surgery (47%) mainly due to axillary clearance following frozen section evaluation of the sentinel nodes (27).…”
Section: Discussionsupporting
confidence: 91%
“…However, the reintervention rate in the current series was only 6.2%, supporting our belief that with careful pre-operative evaluation of the axillary lymph nodes by ultrasound and considering further criteria of risk for axillary node metastases (7,9), it is possible to select breast cancer patients with a reasonably low risk of lymph node metastases, that may safely benefit from this minimally invasive surgical approach. Indeed, previous studies on the same subject not using axillary ultrasound in the preoperative assessment, reported much higher reintervention rates, ranging from 28% to 40% (19,22). After the publication of the ACOSOG Z0011 (29) and IBCSG 23-01 trials (30) and the diffusion of the American Society of Clinical Oncology clinical practice guideline updated in 2016 (31), pointing out the futility of lymphadenectomy even in the presence of metastases in the sentinel lymph node, the traditional concept of ALND in breast cancer is currently questioned (32).…”
Section: Discussionmentioning
confidence: 95%
“…In our setting as well, cost reduction and the need to free limited bed space were the motivations for implementing this concept. Although much less than figures from developed countries, 24,25 the cost savings of~40 USD indirect cost of care in a country where the majority live below 1 USD per day is quite significant.…”
Section: Discussionmentioning
confidence: 84%
“…Second, the policy cost-effectiveness will be calculated for the Short Stay Programme based on prospective data from breast cancer surgery patients. The cost-effectiveness analysis will use the same methodology as in the primary implementation study [19]. Third, the determinants of sustainability will be explored by means of in-depth semi-structured interviews with relevant stakeholders and external change agents.…”
Section: Methodsmentioning
confidence: 99%
“…In the current study two Dutch implementation cases are used for research on sustainability and its determinants (Additional file 1 and Additional file 2). A Short Stay Programme (MaDO) was implemented in breast cancer surgery in 4 early adopter hospitals by means of a hospital tailored implementation strategy [19-22], and the Enhanced Recovery After Surgery (ERAS) programme in colonic surgery was implemented in 33 hospitals by means of a generic implementation strategy [23,24]. As a result of these efforts (Table 1), both cases showed improved short-term results in terms of hospital length of stay.…”
Section: Introductionmentioning
confidence: 99%